Transplantation of Ultra-Long Cross-Donor Conjoined Perforator Flaps with Multiple Blood Supply Sources for Wound Repair - Liu, Zhijin; Liu, Shengzhe; Cheng, Junnan; Yang, Lin; Zhang, Tao; Ju, Jihui; Hou, Ruixing (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2023)
Objective There are reports about the surgical method and clinical efficacy of using ultra-long cross-donor perforator skin flap transplantation with multiple blood supply sources to repair wounds.Method Between January 2013 and March 2019, 29 wounds were repaired using ultra-long skin flaps from the donor site of the chest, abdomen and anterolateral thigh. All patients were followed up on a regular basis with a view to the following: appearance of skin flap, function of recipient area and healing of donor area.Result After the operation, all 28 skin flaps were fine. On the fifth day after the operation, one case of a 47-cm anterolateral thigh flap had dark skin color in the distal-most area measuring about 5 cm×4 cm, and the incision showed slow bleeding. In 11 cases, linear scars with soft edges and no obvious contractures were left in the donor area of the chest and abdomen. Eighteen cases with lateral femoral donor sites healed successfully, with linear scars forming without contracture. Three cases with lateral femoral donor sites had wide linear scars that were slightly above skin level and exhibited no contracture.Conclusion Transplantation of ultra-long conjoined cross-donor perforator flaps with multiple blood supply is beneficial to wound repair and worthy of clinical promotion.
Keywords: Multiple blood supply; cross-donor area; conjoined flap; perforator flap